Demographic Dividend and Economic Growth: An Empirical Study of Transitional India - Preeti Gupta, Ramesh Chander (European Economic Letters (EEL), 2024)
Demographic transition results in different age structures of the population. These different age groups have different economic behaviour and because of this, age composition change is important for growth of country and working age group have most positive impact on growth. A ‘window of opportunity’ is created when growth of working age population is higher than growth of total population. This enhanced working age population share is called as ‘demographic dividend.’ In this background, this paper tries to examine how demographic dividend of a country impacts its economic growth. Here, we have selected 20 major Indian states as the representative of whole country to see the relationship between two variables demographic dividend and economic growth by using fixed effect model from a time period of 2011 to 2020. The results from the panel data analysis presents that relation between demographic dividend and economic growth is significant and positive.